Tissue-specific and developmentally regulated expression of a chimeric actin-globin gene in transgenic mice. - Shani, M (1986)
A chimeric plasmid containing about 2/3 of the rat skeletal muscle actin gene plus 730 base pairs of its 5' flanking sequences fused to the 3' end of a human embryonic globin gene (D. Melloul, B. Aloni, J. Calvo, D. Yaffe, and U. Nudel, EMBO J. 3:983-990, 1984) was inserted into mice by microinjection into fertilized eggs. Eleven transgenic mice carrying the chimeric gene with or without plasmid pBR322 DNA sequences were identified. The majority of these mice transmitted the injected DNA to about 50% of their progeny. However, in transgenic mouse CV1, transmission to progeny was associated with amplification or deletion of the injected DNA sequences, while in transgenic mouse CV4 transmission was distorted, probably as a result of insertional mutagenesis. Tissue-specific expression was dependent on the removal of the vector DNA sequences from the chimeric gene sequences prior to microinjection. None of the transgenic mice carrying the chimeric gene together with plasmid pBR322 sequences expressed the introduced gene in striated muscles. In contrast, the six transgenic mice carrying the chimeric gene sequences alone expressed the inserted gene specifically in skeletal and cardiac muscles. Moreover, expression of the chimeric gene was not only tissue specific, but also developmentally regulated. Similar to the endogenous skeletal muscle actin gene, the chimeric gene was expressed at a relatively high level in cardiac muscle of neonatal mice and at a significantly lower level in adult cardiac muscle. These results indicate that the injected DNA included sufficient cis-acting control elements for its tissue-specific and developmentally regulated expression in transgenic mice.